Rural Roads and Local Market Development in Vietnam - Mu, Ren; van de Walle, Dominique (World Bank, Washington, DC, 2012)
The authors assess impacts of rural road rehabilitation on market development at the commune level in rural Vietnam and examine the variance of those impacts and the geographic, community, and household factors that explains it. Double difference and matching methods are used to address sources of selection bias in identifying impacts. The results point to significant average impacts on the development of local markets. They also uncover evidence of considerable impact heterogeneity, with a tendency for poorer communes to have higher impacts due to lower levels of initial market development. Yet, poor areas are also saddled with other attributes that reduce those impacts.